Question
upstudy study bank question image url

b) \[ \begin{array}{l} x+2 y=4 \\ x-2 y=0 \end{array} \] d) \[ \begin{array}{l} x+4 y=14 \\ 3 x+2 y=12 \end{array} \]

Ask by Norton Mcfarlane. in South Africa
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are: - For part b: x = 2 and y = 1 - For part d: x = 2 and y = 3

Solution

Let's solve each system step by step. b) Equations:   1) x + 2y = 4   2) x − 2y = 0 Step 1: Add equations (1) and (2) to eliminate y:   (x + 2y) + (x − 2y) = 4 + 0   2x = 4  ⇒  x = 2 Step 2: Substitute x = 2 into equation (1):   2 + 2y = 4   2y = 4 − 2 = 2  ⇒  y = 1 Thus, the solution is x = 2 and y = 1. d) Equations:   1) x + 4y = 14   2) 3x + 2y = 12 Step 1: Solve equation (1) for x:   x = 14 − 4y Step 2: Substitute x = 14 − 4y into equation (2):   3(14 − 4y) + 2y = 12   42 − 12y + 2y = 12   42 − 10y = 12 Subtract 42 from both sides:   −10y = 12 − 42 = −30 Divide by −10:   y = (−30)/(−10) = 3 Step 3: Substitute y = 3 back into equation (1):   x + 4(3) = 14   x + 12 = 14   x = 14 − 12 = 2 Thus, the solution is x = 2 and y = 3. Summary:  b) x = 2, y = 1  d) x = 2, y = 3

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the first system of equations, you can either use substitution or elimination. Here, let's use elimination. Adding the two equations: 1) \( x + 2y = 4 \) 2) \( x - 2y = 0 \) Adding them gives \( 2x = 4 \), so \( x = 2 \). Plugging \( x \) back into either equation (let's choose the first one) gives \( 2 + 2y = 4 \), leading us to \( 2y = 2 \) or \( y = 1 \). Thus, the solution is \( (2, 1) \). Now for the second system: 1) \( x + 4y = 14 \) 2) \( 3x + 2y = 12 \) Let's solve for \( x \) in the first equation: \( x = 14 - 4y \). Substitute \( x \) into the second equation: \( 3(14 - 4y) + 2y = 12 \) Distributing gives \( 42 - 12y + 2y = 12 \) or \( 42 - 10y = 12 \). Solving for \( y \) leads to \( 10y = 30 \), so \( y = 3 \). Plugging \( y \) back into \( x = 14 - 4(3) \) yields \( x = 2 \). Thus, the solution is \( (2, 3) \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy